Identification of a region in p47phox/NCF1 crucial for phagocytic NADPH oxidase (NOX2) activation. Issue 3 (27th December 2012) - Sareila, Outi; Jaakkola, Noora; Olofsson, Peter; Kelkka, Tiina; Holmdahl, Rikard
Abstract : The p47phox (NCF1) variant expressed in Ncf1 m1J mice is defective in activating the NOX2 complex to produce ROS. Abstract : A point mutation in the mouse Ncf1 m1J gene decreases production of ROS by the phagocytic NOX2 complex. Three mRNA splice variants are expressed, but only one is expressed as a protein, although at lower levels than the WT NCF1 (also known as p47phox). Our aim was to investigate whether the mutant p47phox, lacking 8 aa, is active, but as a result of its low expression, ROS production is decreased in Ncf1 m1J mice, or whether the mutant p47phox completely lacks the capability to activate the NOX2 complex. The p47phox mutant (Δ228–235), which was equal to the protein in Ncf1 m1J mice, failed to activate the NOX2 complex. When the deleted region was narrowed down to 2 aa, the p47phox protein remained inactive and failed to translocate to the membrane upon activation. Single amino acid substitutions revealed Thr233 to be vital for ROS production. Residues Tyr231 and Val232 also seemed to be important for p47phox function, as p47phox_Y231G and p47phox_V232G resulted in a >50% decrease in ROS production by the NOX2 complex. In addition, we identified the epitope of the D‐10 anti‐p47phox mAb. In conclusion, the p47phox protein variant expressed in Ncf1 m1J mice is completely defective in activating the NOX2 complex to produce ROS, and the effect is dependent on SH3 region amino acids at positions 231–233, which are vital for the proper assembly of the NOX2 complex.